Modelling Study of Pile Group Foundation by Including Lateral Load in Clay Soil - Muhammad Reza Imansyah; Widjojo Adi Prakoso; Mulia Orientilize (Indonesian Geotechnical Journal, 2023)
Indonesia’s geographical condition causes earthquakes to occur more frequently. This study aims to investigate pile group response under earthquake loading by performing pushover analysis. Since clay soil is dominant and widespread in Indonesia, the study focused on pile group embedded in single layer of clay. The undrained shear strength (Su) parameters of the clay are varied from 20 kPa, to 100 kPa with 20 kPa intervals. The pile and soil were modelled by Beam-on-Nonlinear-Winkler-Foundation (BNWF), and the soil was presented as a series of Winkler springs using the nonlinear p-y method. The analysis was conducted with a finite element method (FEM) software, OpenSees. The pile was modelled as a fiber section, where the transversal and longitudinal reinforcement can be considered. The research found that the soil’s Su affects the ductility and formation of plastic hinge. Greater Su resulted in higher ductility and occurrence of plastic hinge. Higher Su was also found to increase the internal force experienced in the pile, as well as lead to higher group efficiency factor. There was no shear failure detected in the results, but bending failure happened at the lead pile in Su 100 kPa. The overturning moment phenomenon occurred on the pile group in Su 20 kPa and 100 kPa. For Su = 20 kPa, this phenomenon is caused by the middle pile and rear pile, which did not have optimal performance. Bending failure at the lead pile led to the phenomenonin Su 100 kPa.